The RNA-binding protein SRSF1 is a key cell cycle regulator via stabilizing NEAT1 in glioma. (August 2019) - Zhou, Xuexia; Li, Xuebing; Yu, Lin; Wang, Run; Hua, Dan; Shi, Cuijuan; Sun, Cuiyun; Luo, Wenjun; Rao, Chun; Jiang, Zhendong; Wang, Qian; Yu, Shizhu
Abstract: The relevance of RNA processing has been increasingly recognized in a variety of diseases. We previously identified serine/arginine-rich splicing factor 1 (SRSF1) as an oncodriver in glioma via splicing control. However, its splicing-independent roles and mechanisms are poorly defined in glioma. In this study, by integrating the data mining of SRSF1 -co-expressed genes, SRSF1-affected genes and experimental studies, we demonstrated that SRSF1 was the most highly expressed SRSF in the 9 tumor types tested, and it was a crucial cell cycle regulator in glioma. Importantly, we identified nuclear paraspeckle assembly transcript1 ( NEAT1 ), an upregulated long non-coding RNA (lncRNA) in glioma, as a target of SRSF1. Endogenous NEAT1 inhibition resembled the effect of SRSF1 knockdown on glioma cell proliferation by retarding cell cycle. Mechanistically, we proved that SRSF1 bound to NEAT1 and facilitated its RNA stability. The positive correlation between SRSF1 and NEAT1 levels in cancers further supported the positive regulation of NEAT1 by SRSF1. Collectively, our results provide novel insights on the splicing-independent mechanisms of SRSF1 in glioma, and confirm that NEAT1, whose stability maintained by SRSF1, implicates gliomagenesis by regulating cell cycle. Both SRSF1 and NEAT1 may serve as promising targets for antineoplastic therapies.